Prokinetic Agents - Hyo Yeop Song; Sung Won Jung; Yong Sung Kim (Yong Chan Lee, 2022)
Gastrointestinal (GI) prokinetic agents are drugs that increase GI motility and promote the movement of contents in the GI tract by amplifying and controlling the contraction of GI smooth muscle. Currently used prokinetics increase GI motility by acting as a dopamine D2 receptor antagonist (e.g., metoclopramide, domperidone, levosulpiride) and 5-HT4 receptor agonist (e.g., mosapride, prucalopride). Some prokinetics also have a cholinesterase inhibitory property (e.g., itopride), and herb-derived prokinetics (e.g., motilitone) affect multiple receptors. Depending on the type and distribution of receptors on which the prokinetics bind, the effect(s) may be regional or throughout the GI tract. Most prokinetics have been used for functional dyspepsia and gastroparesis because they mainly affect upper GI motility. However, prucalopride, a highly selective 5-HT4 receptor agonist, is used primarily to treat chronic constipation and pseudo-obstruction. Dopamine D2 receptor antagonists also inhibit the D2 receptor in the medulla oblongata chemoreceptor trigger zone; therefore, they can treat nausea and vomiting. However, short term use of dopamine D2 antagonists at an appropriate dose is recommended because of their potential for central nervous system side effects by penetrating the blood-brain barrier. It is necessary to know the mechanism of action, each clinical trial's characteristics, and the side effects of prokinetics to obtain the best clinical outcomes. This article aims to summarize the results of clinical studies related to the impact of currently available prokinetic agents in Korea on GI motility.